KUPU-KUPU DALAM KARYA SENI GRAFIS - Nopri Yandri Asri; Irwan Irwan; Yofita Sandra (Universitas Negeri Padang, 2020)
The creation of this final work aims to visualize the metamorphosis of butterflies in stencil techniques. This work displays the object of a butterfly that is to social criticism. The embodiment method of this final work goes through five stages: preparation, elaboration, synthesis, concept realization, and completion. Author Successfully Realizing 10 works with the title: new life, sweet, short time, life's journey, freedom, life span, inspiration, survival, generation, and success.Keywords: Butterfly, Graphic Art, Cut Out Stencil Print